ROOM RESERVATION APPLICATION AND ADMINISTRATION AT THE HOTEL MATRA - Hariyanto Hariyanto; Sahni Damerianta P. SKom, MM (Jurnal Sistem Informasi, 2000)
This information system is now widely used by the public as information that helps interms of data processing, as well as hotels Matra which data processing has not beenmaximized. With the existence of the information system based on ease ofpreparation room no. Buyer, no. Room type or price and inventory can be more rapid,precise and accurate.By using information systems make the job easier and can save time and effortemployees Hotel Marta. In studying information systems which will need a strongtheoretical foundation for supporting information to be used, so that in running itsdata processing errors can be avoided, for supporting a covering used DFD contextdiagram, diagram of zero, ERD, normalization da file specification.